Teacher Attitudes Based on Gender and Experience - Eva Imania Eliasa; Ilfiandra; Suwarjo; Budi Astuti; Aprilia Tina Lidyasari; Sahril Buchori; Natri Sutanti; Indriyana Rachmawati; Nadia Aulia Nadhirah; Afanin Halqim (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
Teachers, as key agents in peace education within schools, are expected to promote the development of an effective peace vision and to possess strong peace pedagogy in order to cultivate a peaceful school climate. This study aims to quantitatively describe the role of teachers in Indonesia in fostering a culture of peace in schools. The research employed a qualitative approach with a descriptive qualitative design. The sample consisted of 1,067 Indonesian teachers who provided informed consent prior to participation. Data were collected using the Teacher Peace Scale administered through Google Forms. Descriptive qualitative analysis was conducted to identify differences in teachers’ knowledge, attitudes, and skills related to peace concepts. The findings indicate that there were no significant variations in knowledge, attitudes, or skills as a function of training duration. Nevertheless, teachers are required to develop adequate knowledge, attitudes, and competencies related to peace in order to promote a peaceful school culture. These competencies constitute essential foundational capital for teachers in educating students about peace in school settings. Furthermore, the development of comprehensive and integrated peace competencies is expected to strengthen a culture of peace among teachers, enabling them to deliver peace education effectively and to recognize, analyze, and guide students’ behaviors constructively. The implications of this study provide empirical insights into the extent to which gender differences and teaching experience influence teachers’ attitudes toward instilling peace values in schools.